Pakistan Army Green Book 2011 - Pakistan Army; Editorial Board : Brig. Khushnud Iqbal; Lt. Col. Zafar Iqbal and Lt. Col.Qamar UI Islam (GHQ, Rawalpindi Pakistan Army, 2011)
Content of the book are the writer' personal views and are not to be taken as official opinion/policy
Include Color Illustration
Keywords: Pakistan. Army -- Pakistan. -- Army -- Periodicals